A Relational Sociological Approach to Active Ageing: The Role of Intergenerational Relations and Social Generativity - Meda, Stefania Giada; Rossi, Giovanna; Bramanti , Donatella (Stan Rzeczy, 2017)
This paper considers the concept of active ageing from the perspective of relational sociology. Active ageing is the process of optimizing opportunities for health, participation, and security in order to enhance quality of life as people age. Ageing occurs in a relational network (the family, society), with a whole range of reciprocal mutual interactions (support, care, etc.). Starting from an operationalization of the relational components (Donati 2011) of the active ageing process, SHARE data were considered, as well as data collected for the Italian survey Non mi ritiro: l’allungamento della vita, una sfida per le generazioni, un’opportunità per la società (“I’m Not Withdrawing: The Lengthening of Life, a Challenge for the Generations, an Opportunity for Society”, 2013–2014, N=900), in which the way Italians and other Europeans face ageing was explored. Finally, the focus was ona sub-sample of older adults active in various relational networks, such as their families (grandparents and caregivers aged 65+ of the older generation) and third-sector organizations. By embracing a relational (intergenerational) lens it was possible to grasp the differentiation that characterizes the ageing process, the transformations and standstills of individuals, as well as different orientations and ideas that facilitate or hinder the path to active ageing.